2004
DOI: 10.1002/lapl.200310024
|View full text |Cite
|
Sign up to set email alerts
|

Corollary to Noether's theorem about the conservation of angular momentum and spin in theories that are dealing with strong laser fields

Abstract: We have shown that Noether's theorem [16] has a corollary which proves non-conservation of angular momentum and spin in "mixed" theories (the ones that combine classical and quantum approach). As laser field is treated classically and atoms with which it interacts must be treated as quantum objects (see, for instance [1], where the ADKtheory is described, which we take as a represent of "mixed" theories), it is shown that in such theories the law of conservation of the 4-angular momentum tensor is broken. As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…We are offering a possible explanation why! It has been stressed more than once that theories describing behavior of atoms in strong laser fields treat an atom as quantized object and electromagnetic field classically [5]. We already suggested that these theories should be called "mixed".…”
Section: Introductionmentioning
confidence: 96%
“…We are offering a possible explanation why! It has been stressed more than once that theories describing behavior of atoms in strong laser fields treat an atom as quantized object and electromagnetic field classically [5]. We already suggested that these theories should be called "mixed".…”
Section: Introductionmentioning
confidence: 96%